Characteristic Of Shrimp Catch Of Sondong In Kampung Laut Village Tanjung Jabung Timur Regency - Depison Depison; Bella Pratiwi Putri; Lisna Lisna (Jurnal Perikanan dan Kelautan, 2020)
Kampung Laut is an area where fishing activities are done. Fishermen get profit by catching shrimp. One of the tools used is sondong. The kinds of shrimp that are widely catched in there are lime, dogol, and yellow shrimp. The important thing in catching shrimp is paying attention to its size. The suitable size for the catching is a goal in the management of good fisheries to conserve shrimp resources in water. This study aims to see the characteristics of the shrimp caught by sondong in Kampung Laut, Tanjung Jabung Timur Regency. Method used is simple random sampling, the number of shrimp samples taken is 10% of the total catch per shrimp species. The results showed that the lime shrimp taken with a sondong fishing tool in the Kampung Laut, collected 9,10-14,80 cm with a percentage of shrimp worth capturing 61%. The size of the dogol shrimp caught in the range of 8.70-14.00 cm with a percentage of shrimp worth catching 60%. The size of the yellow shrimp is around 7.50-12.00 cm with the percentage of shrimp worth catching 53%. The correlation coefficient value of lime shrimp weight length is 2.89, dogol shrimp 2.30, and yellow shrimp 2.27. The conclusion is shrimp taken with sondong fishing tool in Kampung Laut has various sizes, ranging from small to large sizes. The growth patterns of lime shrimp, dogol shrimp, and yellow shrimp showed negative allometric growth properties. Percentage of shrimp size that is catchable is greater compared to uncatchable shrimp.